Profile of Sugarcane Growers of Southern Karnataka and their Association with Crisis Management Behaviour - Sanjay, V. C.; Mondal, Sabita; Hui, Chandan Kumar; Rai, Ushia; Rai, Birat (International Journal of Bio-resource and Stress Management, 2025)
The study was conducted during October, November month of 2022 and January month of 2023 in Mandya and Mysore districts, Karnataka state, India to study the profile of sugarcane growers and to find out the association between the profile of the sugarcane growers and their crisis management behaviour in Southern Karnataka. Mandya and Mysore districts of Karnataka were purposively selected and talukas, villages and respondents were selected through multistage simple random sampling. Two talukas each from Mandya and Mysore districts along with two villages from each taluka were selected randomly. From each village, 15 sugarcane growers with a minimum of five years of experience in sugarcane cultivation were selected randomly which made a sample size of 120 respondents. Data were collected using a structured interview schedule through the physical interview method. Statistical tools such as mean, frequency, percentage, SD, correlation and stepwise regression were used for data analysis. The findings revealed that sugarcane growers belonged to the category of middle-aged farmers with small landholdings with moderate income and possessed 10-20 years of farming experience. They generally had low or no formal education but exhibited a medium level of information-seeking behaviour, innovativeness, self-confidence, scientific orientation and credit support. They demonstrated high levels of cosmopoliteness, farming commitment and deferred gratification but had a moderate perception of crisis with a favourable attitude. Age, farming experience, income, information seeking behaviour, innovativeness, scientific orientation, farming commitment, deferred gratification and attitude towards crisis were the variables found to have a positive and significant association with the crisis management behaviour of farmers. Cosmopoliteness, annual income, farming experience, scientific orientation and attitude explained 40.00% of the variance in crisis management behaviour.